2020
DOI: 10.1016/j.seizure.2020.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognosis in a large paediatric cohort with status epilepticus

Abstract: To describe the aetiology, clinical features, and short-term outcomes of children with status epilepticus (SE), in particular super-refractory SE (SRSE), by a nationwide multicentre study in China. Methods: In this retrospective study, inpatient children with SE were identified from neurology departments and paediatric intensive care units from 44 hospitals in 27 provinces of China between 2013 and 2015. Clinical data were exported from the Hospital Information System. Results: Clinical records from children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…People with DRE experience significantly more comorbidities, including depression, seizure-related injuries, and neurological deficits than those without epilepsy or with epilepsy that responds to treatment [4,5], and have significantly higher mortality risk [6,7]. DRE is also associated with sudden unexplained death in epilepsy (SUDEP) which represents a major cause of death in this population [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…People with DRE experience significantly more comorbidities, including depression, seizure-related injuries, and neurological deficits than those without epilepsy or with epilepsy that responds to treatment [4,5], and have significantly higher mortality risk [6,7]. DRE is also associated with sudden unexplained death in epilepsy (SUDEP) which represents a major cause of death in this population [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Infection is a risk factor for both pediatric stroke [20][21][22] and status epilepticus. 23,24 The decrease in encounters for these diagnoses could reflect an overall decrease in exposure to typical childhood viral illnesses. Additionally, common provoking factors for seizures and status epilepticus including poor sleep and medication adherence challenges could have improved when children were out of school and home with caregivers more consistently.…”
Section: Discussionmentioning
confidence: 99%
“…11 A nationwide multicentre study in China revealed that the most common known SE etiology was acute symptomatic etiology (42.8%) and 50.2% of SE was caused by epilepsy of unknown etiology. 12 Valencia and colleagues stated that EEG is helpful in the great majority of their patients for supporting the diagnosis of epileptic seizures. 13 The 2014-2017 period included more patients with unknown reason epilepsy (36.5%) compared to 2010-2013 (19.8%).…”
mentioning
confidence: 99%